Transformasi Politik Hukum Rumah Sakit: Reformasi Undang-Undang Kesehatan, JKN, dan Komersialisasi Layanan: Hospital Legal Policy Transformation: Health Law Reform, NHI, and Service Commercialization - Azzahra, Mutia; Yusniani, Baiq Dewi; Anugrah , M. Reza (Jurnal Hukum dan Etika Kesehatan, 2026)
Regulatory reform in the health sector through amendments to the Health Law and the strengthening of the National Health Insurance (JKN) scheme has had significant implications for the direction of legal policy and the business models of hospitals in Indonesia, both stateowned hospitals (BUMN, TNI, Polri) and private hospitals. These regulatory changes raise a fundamental question regarding the orientation of hospital administration: whether it remains focused on public service or is increasingly driven toward commercialization. This study aims to analyze the transformation of legal policy that affects hospital governance, financing, and service orientation following the reform of health regulations. The research employs a normative juridical approach by examining statutory regulations, health policies, academic literature, and secondary data related to the implementation of JKN and hospital practices. The findings indicate that regulatory reform has created new dynamics: on the one hand, it promotes improved access and public service standards through JKN, yet on the other hand, it reinforces the logic of the health industry that prioritizes cost efficiency and profit orientation, particularly within private and stateowned hospitals. These findings highlight the persistent tension between social missions and economic interests in the administration of hospitals in Indonesia.